Gender dynamics in dairy production in Kenya: A literature review - Gallina, Ambra (2016)
This literature review serves as a background document to better understand gender roles and dynamics in the dairy sector in Kenya and thus aims to inform research activities on the gender dimensions of mitigation options, such as sustainable dairy intensification. Technology change has strong gender and labor implications, as it typically involves renegotiation, reassignment, or deepening of roles and responsibilities within households. It can also alter traditional patterns of access to resources such as milk, land, and income. Clarifying gender issues is critical to inform programs and policies for effective design and delivery of mitigation technologies among smallholder households, and to ensure that the benefits of mitigation technologies reach women and men fairly, and thus contribute to both poverty reduction and sustainability.